Coordenação pedagógica e educação continuada dos professores do ensino fundamental: realidade ou utopia em Cachoeira do Sul? - Bordignon, Andressa (2024)
This study, from the Professional Master’s Course, of the Postgraduate Program in Public Policies and Educational Management at the Federal University of Santa Maria in Research Line 1 - Policies and Management of Basic Education, linked to Interfaces, group of Studies in Education, Technologies and Society addresses the issue of pedagogical coordination in the continuing education of elementary school teachers in Cachoeira do Sul. Its general objective is to analyze the performance of the pedagogical coordinators in the training of teachers in the municipal public network of fundamental education in Cachoeira do Sul through current public policies. On main objectives it prioritizes: to characterize the pedagogical coordinators who serve municipal public elementary schools in Cachoeira do Sul; to investigate the implications of the BNC continuing formation on the work of the pedagogical coordinator; to understand the conceptions of the pedagogical coordinator about training for the professional development of teachers; proposing a space for continuing education for the coordinators to work in the municipality and, based on this, create an action protocol for them to start a process of continuing education with groups of teachers. It is based on a research with a dialectic and qualitative approach - the case of study type, to be carried out in municipal elementary schools that attend the final years with the pedagogical coordinators and the pedagogical coordinators, using bibliographical research and semi-structured interviews. The theoretical framework is organized based on authors such as Libâneo (2003, 2012), Placco and Almeida (2012, 2013, 2015), Lima (2001) and others. The idealized product will be a Continuing Education Program for Pedagogical Coordinators and an Action Protocol for pedagogical coordination to organize the continuing education of teachers in schools, with the purpose of helping these managers in exercising their functions, contributing to continuing education in schools in a way that is meaningful for all educators.